PREVALENCE OF BOVINE VIRAL DIARRHEA VIRUS AND PERSISTENTLY INFECTED CATTLE IN THE PROVINCE OF ESPINAR, CUSCO - Cárdenas A., César (2011)
The prevalence of bovine viral diarrhea virus (BVDV) was evaluated in 406 cattle ofboth sexes and older than 6 months. Animals belonged to 114 small farmers from threerural communities of the province of Espinar, Cusco, Peru. Blood samples were collectedaccording to three age groups (6-12, 13-23, >24 months old). Serum samples were testedfor antibodies against BVDV using the viral neutralization test. The 56.2 ± 4.8% (228/406)of samples had antibodies against BVDV. Persistently infected animals were not detected.Antibodies were present in the three age groups, but the highest prevalence (65.4%) was detected in animals older than 24 months of age. The 51.3% (20/39) of young and adultbulls had antibodies against BVDV. Antibodies titers varied from 2 to >256, and hightiters (128 to >256) were detected in 42.1% of animals of 13 to >24 months of age. The86.8% (99/114) of the small farmers had at least one animal seropositive to BVDV.